Foot rot (Phytophthora nicotianae) in Cactus Pear (Opuntia spp.) Genotypes under Arid Conditions - Nallathambi, P; Umamaheshari, C; Singh, R S (Annals of Arid Zone, 2016)
Foot rot caused by Phytophthora nicotianae has been observed as a major disease in the establishment of cactus pear (Opunita spp.) under arid conditions. Foot rot incidence was prevalent in 23.5% of the germplasm collections during the months of August and November. The fungal pathogen could infect the c1adodes through infected planting materials as well as through soil. Soil drenching with 0.1% metalxyl plus mancozeb (Ridomil) and dipping of cut ends of cactus pads in fungicide at the time of planting were found effective in control of the foot rot.